The Effect of Tulathromycin Treatment on Antioxidant Vitamins in Montofon Calves with Pneumonia - Ragbetli, C.; Tanritanir, P.; Yoruk, I.; Cay, M. (Medwell Online, 2009)
The purpose of this study is to examine changes in some vitamin levels and clinical symptoms of treatment with tulathromycin in Montofon calves with pneumonia. For this purpose, 30 calves exhibiting clinical sings of pneumonia such as fever >39 degrees C, elevated respiratory rate >40 (min(-1)), pulsation >100, cough, lack of appetite, nasal flaring, mandibular lymph node enlargement, respiratory difficulties and nasal discharge were studied. A control group of 20 healthy calves were also studied. Blood samples were collected from the diseased calves before and after treatment with tulathromycin (Draxxin-Pfizer), as well as from the healthy calves in order to determine retinol (mu g mL(-1)), alpha-tocopherol (mu g dL(-1)) and vitamin D-3 (mu g dL(-1)) levels by High Performance Liquid Chromatography (HPLC). Compared to the control group, there were increase of both retinol and alpha-tocopherol levels in the diseased animals and the increase in retinol levels were significant (p<0.001). Vitamin D-3 levels weren't affected in the diseased animals (p>0.05). Abnormal rectal temperatures, respiratory rates and pulsation levels decreased significantly (p>0.001).
Keywords: Pneumonia; vitamin levels; calf; tulathromycin; tulathromycin; montofon calves